1993
DOI: 10.1093/bja/71.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Tropisetron for Postoperative Nausea and Vomiting in Patients After Gynaecological Surgery

Abstract: In a double-blind study, we have compared the prophylactic antiemetic effect of tropisetron 5 mg (Navoban, a 5-HT3 receptor antagonist) with that of placebo, both given as a short i.v. infusion approximately 15 min before wound closure in patients undergoing gynaecological surgery. Perioperative anaesthetic care was standardized and patients were observed for at least 24 h after operation. The 35 patients given tropisetron and 34 given placebo treatment were well matched for characteristics. Vomiting occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 11 publications
2
13
1
1
Order By: Relevance
“…Our baseline incidence of PONV (72%) in the placebo group is consistent with the incidence reported in previous studies for patients who underwent other surgical procedures. 7,1~ Zomers et al 7 noted that nausea and vomiting occurred in 88% and 59%, respectively, in the placebo-treated patients. Similarly, Larijani et al 12 reported that 72% of their patient in the placebo group suffered from PONV.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our baseline incidence of PONV (72%) in the placebo group is consistent with the incidence reported in previous studies for patients who underwent other surgical procedures. 7,1~ Zomers et al 7 noted that nausea and vomiting occurred in 88% and 59%, respectively, in the placebo-treated patients. Similarly, Larijani et al 12 reported that 72% of their patient in the placebo group suffered from PONV.…”
Section: Discussionmentioning
confidence: 97%
“…In patients undergoing gynaecological surgery, Zomers et al 7 reported that vomiting occurred in 26% of tropisetron (5 mg)-treated patients compared with 59% of placebo-treated patients (P = 0.006). The incidence of nausea was, respectively, 69% and 88% (P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Tropisetron has an elimination half-life of 8-12 h [136] and has been studied for prevention [137][138][139] and treatment [140] of PONV in adults. Tropisetron has been found effective for prevention of PONV after breast [137] and gynecologic surgery [138] when a 5-mg IV dose was administered prior to the start of anesthesia [137,138].…”
Section: Tropisetronmentioning
confidence: 99%
“…Tropisetron has been found effective for prevention of PONV after breast [137] and gynecologic surgery [138] when a 5-mg IV dose was administered prior to the start of anesthesia [137,138]. Zomers et al [139] determined that tropisetron 5 mg was effective for prevention of PONV following gynecological surgery. Alon et al [140] determined that tropisetron 2 mg IV was the optimal effective dose for the treatment of PONV following a variety of abdominal and non-abdominal surgeries (table 5).…”
Section: Tropisetronmentioning
confidence: 99%
“…Tropisetron (Table 3) In a randomized, double-blind, placebo-controlled study, the prophylactic antiemetic tropisetron, administered at a dose of 5 mg i.v., effectively reduced the incidence of PONV after gynecologic surgery [51,52]. Capouet et al [53] have compared the efficacy of tropisetron at three different doses (0.5, 2, and 5 mg) with the effect of placebo administered i.v.…”
Section: Introductionmentioning
confidence: 99%